Nursing Care Analysis of Hypertension Through Hypertension Management with Swedish Massage Therapy - Nurlaela, Gina; Taobah Ramdani, Hasbi; Wahyudin (Nursing Case Insight Journal, 2025)
Hypertension is a condition where a person experiences an increase in blood pressure above normal, potentially leading to morbidity and mortality. The aging process is a natural and inevitable phenomenon. Swedish Massage, a method of massaging the entire body surface, has shown effectiveness in lowering blood pressure in elderly individuals with hypertension. This study employs a descriptive analytical method in the form of a literature review to analyze nursing care problems carried out in patients with hypertension. The research was conducted in Tanjung Kamuning Village, Tarogong Health Center, Garut Regency. Implementing Swedish massage nursing care on Mrs. M for 3 days (30 minutes per session) resulted in a decrease in blood pressure from 170/90 mmHg to 159/85 mmHg. Swedish massage therapy can effectively reduce high blood pressure in elderly individuals. It is recommended for application in nursing care for elderly patients with hypertension.